VD_FINDINFO 29/2013/SNR vom 26. April 2013 - VD Tribunal cantonal (2013)
PROPRIÉTÉ PAR ÉTAGES, LÉGITIMATION ACTIVE ET PASSIVE, PERSONNALITÉ, PERSONNE MORALE | 647b CC, 712i CC, 712k CC, 712l CC, 712q CC, 712t al. 1 CC, 712t al. 2 CC, 139 CPC, 265 CPC, 67 LAIEN, 69 LAIEN